2016
DOI: 10.1080/2162402x.2015.1115941
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of LRP5 and LRP6 in dendritic cells enhances antitumor immunity

Abstract: The tumor microenvironment (TME) contains high levels of the Wnt family of ligands, and aberrant Wnt-signaling occurs in many tumors. Past studies have been directed toward how the Wnt signaling cascade regulates cancer development, progression and metastasis. However, its effects on host antitumor immunity remain unknown. In this report, we show that Wnts in the TME condition dendritic cells (DCs) to a regulatory state and suppress host antitumor immunity. DC-specific deletion of Wnt co-receptors low-density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(88 citation statements)
references
References 37 publications
7
81
0
Order By: Relevance
“…The role of Wnt/β-catenin signaling in immune cells in the TME and its effect on host antitumor immunity and tumor-induced immune tolerance remain unknown. Recent studies from several labs have shown that increased levels of Wnts in the TME can initiate paracrine signaling and modulate host antitumor immunity (63, 7175). …”
Section: Wnt/β-catenin Signaling In Dcs Modulates Antitumor Immunitymentioning
confidence: 99%
See 4 more Smart Citations
“…The role of Wnt/β-catenin signaling in immune cells in the TME and its effect on host antitumor immunity and tumor-induced immune tolerance remain unknown. Recent studies from several labs have shown that increased levels of Wnts in the TME can initiate paracrine signaling and modulate host antitumor immunity (63, 7175). …”
Section: Wnt/β-catenin Signaling In Dcs Modulates Antitumor Immunitymentioning
confidence: 99%
“…Mechanistically, this is also due to activation of β-catenin signaling in TME DCs and their ability to up regulate immune-regulatory factors such as IDO, IL-10, and Raldh (63, 71, 73, 75). Furthermore, TME DCs express high levels of IL-10 and TGF-β that promotes immune tolerance through induction of IL-10-producing CD4 + and CD8 + T cells (63).…”
Section: Wnt/β-catenin Signaling In Dcs Modulates Antitumor Immunitymentioning
confidence: 99%
See 3 more Smart Citations